2009
DOI: 10.1093/carcin/bgp077
|View full text |Cite
|
Sign up to set email alerts
|

EGFR pathway polymorphisms and bladder cancer susceptibility and prognosis

Abstract: The epidermal growth factor receptor (EGFR) pathway has recently been appreciated as a central mediator of tumorigenesis and an important drug target; however, the influence of genetic variation in this pathway on bladder cancer is not understood. Pathway activation leads to cell proliferation, angiogenesis and is antiapoptotic. We sought to test the hypothesis that bladder cancer susceptibility and survival are modified by inherited variations in the sequence of the EGFR and its pathway members. We tested ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 55 publications
1
19
0
2
Order By: Relevance
“…These pathways can affect cell proliferation, differentiation, apoptosis, tumor metastasis, angiogenesis, and immune response. In a large case-control study of 857 UBC cases and 1191 controls from New Hampshire, Mason et al found genetic variants of EGFR were associated with increased UBC risk [40]. Moreover, several of the variants also correlated with overall survival in the cases.…”
Section: Candidate Genes and Pathways Associated With Ubc Recurrence mentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways can affect cell proliferation, differentiation, apoptosis, tumor metastasis, angiogenesis, and immune response. In a large case-control study of 857 UBC cases and 1191 controls from New Hampshire, Mason et al found genetic variants of EGFR were associated with increased UBC risk [40]. Moreover, several of the variants also correlated with overall survival in the cases.…”
Section: Candidate Genes and Pathways Associated With Ubc Recurrence mentioning
confidence: 99%
“…One of the EGFR SNPs (R521K; rs11543848) is a known functional SNP that alters ligand binding and transmembrane signaling [39]. The variant allele of this SNP decreases receptor tyrosine kinase activation and was associated with increased UBC survival [40]. In another large case-control study of 1157 UBC cases and 1157 matched controls, Castillejo et al examined the association of three SNPs in TGFB1 and three SNPs and one insertion/deletion polymorphism of TGFBR1 with UBC risk and clinical outcome(tumor relapse, progression, and survival) [41].…”
Section: Candidate Genes and Pathways Associated With Ubc Recurrence mentioning
confidence: 99%
“…Blocking of EGFR-EGF interaction has been demonstrated to arrest bladder cancer cells growth, resulting in tumor cell death, and limit apoptosis in vitro [31,32]. Several activating mutations of the kinase domain or truncating mutations of the extracellular domain have been described in bladder cancer but few are expected to modulate response profile to EGFR blocking [33,34]. Thus, antibody-based therapeutic blockade of EGFR or its ligands represents a new and exciting option for bladder cancer therapy.…”
Section: Epidermal Growth Factor Receptor (Egfr/erbb1)mentioning
confidence: 99%
“…Os ligantes vinculam-se ao EGFR ativando a transdução de sinal que regula para cima os fatores de transcrição, levando ao estímulo do crescimento celular. 23 Outra característica peculiar do EGF é sua potente ação mitogênica no mesotélio ovariano 24 , local onde há uma significativa expressão desse fator de crescimento e de seu receptor. 25 Dependendo do tipo de célula, a ligação do EGF ao EGFR induz várias cascatas ativadoras que podem resultar em várias respostas celulares que incluem mitose, secreção de proteínas, diferenciação e aquisição de motilidade.…”
Section: Fator De Crescimento Epidermal (Egf) E Seus Receptoresunclassified